Effect of Procurement Outsourcing Practices on Operational Performance of RwandAir - Rugina, Thomas; Akims, Amos (Global Journal of Purchasing and Procurement Management, 2024)
Purpose: The primary aim of this study is to explore how procurement outsourcing practices impact the operational performance of RwandAir in Rwanda. Specific objectives include evaluating the influence of supplier, warehouse, material, and logistics outsourcing on the operational performance of RwandAir. Methodology: The research was grounded in theories including Transaction Cost Economics (TCE), Principal Agency Theory, Resource Dependency Theory, and Queuing Theory. The study employs a descriptive survey design with both quantitative and qualitative methods for data collection. Quantitative data was collected via surveys, and qualitative insights were gathered through semi-structured interviews. Documentary analysis also supplemented the primary data. The target population consists of 148 individuals from various categories involved in RwandAir, with purposive sampling ensuring representation from different procurement categories. A sample size of 109 was determined using Slovin's formula. Data analysis includes descriptive statistics, inferential tests (regression analysis), and thematic analysis. Findings: The findings reveal significant relationships between various types of outsourcing and organizational performance, as shown by the regression coefficients. Supplier outsourcing had the strongest positive impact on performance (coefficient = 0.786, p < 0.001). Warehouse outsourcing contributed positively (coefficient = 0.165, p = 0.015), material outsourcing showed a modest effect (coefficient = 0.133, p = 0.046), and logistics outsourcing also had a significant impact (coefficient = 0.380, p < 0.001). The results suggest that effective outsourcing strategies, especially in supplier and logistics areas, enhance operational efficiency. Unique Contribution to Theory, Practice and Policy: The study recommends that RwandAir prioritize and strategically implement outsourcing in supplier, warehouse, material, and logistics operations to enhance overall performance and operational efficiency. Future studies should investigate the long-term effects of outsourcing strategies on organizational performance across different industries to understand their sustainability and adaptability in dynamic market environments.